(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2023)
The paper is divided into two main aims. In the first part, it wants to investigate the presence of thermal imaging in the context of contemporary visual culture, especially during the Covid-19 pandemic, when thermal imaging widely demonstrated how currently optics models of vision are increasingly accompanied by thermal models of visualisation. The result of the latter is thermography: at the same time, a process that transforms our epistemic relationship with reality, extending the possibilities of visualising information beyond the limits of the visible spectrum; and an image that maintains the indexical bound with its referent, but that is conceived as the outcome of an elaborated and displayed dataset. In the second part, the paper focuses on the artistic field in which thermal vision gained further relevance in the context of the pandemic. On the one hand, the artists have criticised and deconstructed it; on the other hand, they have relaunched its use in a biopolitical horizon, such as in the case of the photographic project Virus (2020), in which Antoine d’Agata roamed the deserted streets of Paris and visited some intensive care units with a thermal camera, during the first national lockdown in 2020.